2011
DOI: 10.3945/ajcn.110.008490
|View full text |Cite
|
Sign up to set email alerts
|

The relation between acute changes in the systemic inflammatory response and plasma 25-hydroxyvitamin D concentrations after elective knee arthroplasty

Abstract: Plasma concentrations of 25(OH)D decrease after an inflammatory insult and therefore are unlikely to be a reliable measure of 25(OH)D status in subjects with evidence of a significant systemic inflammatory response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
225
2
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 268 publications
(241 citation statements)
references
References 30 publications
11
225
2
3
Order By: Relevance
“…This phenomenon seems to be remarkably stronger in older than younger individuals (Börgermann et al 2012). However, 25(OH)D concentrations remain low 3 months after surgery (Reid et al 2011) despite the normalization of CRP status, suggesting that factors other than inflammation may be responsible for the postsurgical decline in vitamin D.…”
Section: Discussionmentioning
confidence: 98%
“…This phenomenon seems to be remarkably stronger in older than younger individuals (Börgermann et al 2012). However, 25(OH)D concentrations remain low 3 months after surgery (Reid et al 2011) despite the normalization of CRP status, suggesting that factors other than inflammation may be responsible for the postsurgical decline in vitamin D.…”
Section: Discussionmentioning
confidence: 98%
“…This period of follow-up and resolution of inflammation matches our study and represents six elimination half-lives of 25(OH)D which is long enough for a new 25(OH)D equilibrium. Reid et al 7 excluded the possibility that the fall in 25(OH)D was due to inflammation, fall in vitamin D binding protein and iatrogenic dilution.…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple potential explanations, including differential compliance, malabsorption, increased losses (eg, capillary leak), and altered hepatic or end-organ metabolism. [118][119][120][121][122] Together, these findings suggest that rapid normalization of vitamin D status may require consideration of age (or weight), baseline 25(OH)D level, and disease status. Prediction of 25(OH)D levels by using the multivariate model suggested that 50 000 IU is appropriate in young infants, whereas doses in the 300 000 to 600 000 IU range may be required in adolescents.…”
Section: Adverse Event Analysismentioning
confidence: 95%